Philosophical Analysis of Science on The Independent Curriculum as A Knowledge Construction - Ramdhani, Diyan Rifky; Rohanda, Rohanda; Kodir, Abdul (Indo-MathEdu Intellectuals Journal, 2026)
The implementation of the Merdeka Curriculum in Indonesia marks a paradigmatic transformation in the national education system, shifting from an administrative approach toward a deep philosophical transformation. This study aims to analyze the Merdeka Curriculum as a construction of knowledge through the perspective of the philosophy of science, which includes ontological, epistemological, and axiological dimensions. Using a descriptive qualitative method through literature study, this research explores how the curriculum reformulates the nature of knowledge and the position of students. The analysis results show that, ontologically, the Merdeka Curriculum views knowledge as a dynamic-contextual entity and students as autonomous subjects. Epistemologically, there is a shift toward inquiry-constructivist learning through direct experience (learning by doing). Axiologically, the goal of education is directed at shaping a whole human being through the Pancasila Student Profile. The synergy between Progressivism, Constructivism, and the ideas of Ki Hajar Dewantara forms a solid foundation for this curriculum, although challenges such as the readiness of educators' mentality and infrastructure still remain major obstacles in its implementation